ANALISIS KINERJA KEUANGAN PADA PT ASTRA AGRO LESTARI TBK DITINJAU DARI PROFITABILITAS DAN LIKUIDITAS (Studi Empiris pada Perusahaan yang Terdaftar dalam Bursa Efek Indonesia) - Alawiyah, Ucu Tuti Alawiyah (Nusa Putra University, 2020)
In a company must have a financial report. It is used to assess there is no gain or loss in carrying out company activities. The financial performance of a company can be accessed by using 4 tools, including analysis of financial statements of profitability ratios and liquidity ratios. The purpose of this study is to determine whether the presentation of the company's financial statements is in accordance with PSAK No.1 (Revised 2009), to determine the performance of company profitability and liquidity performance. The method used is quantitative descriptive analysis, by analyzing the company's financial performance data from 2013 to 2017 using financial ratio analysis.